Partisipasi Perempuan Muda dalam Wirausaha Keripik Pisang di Gampong Blang Cot Baroh Kecamatan Jeumpa Kabupaten Bireuen - Mayda, Siti Farah (JAROW: Journal of Ar-Raniry on Social Work, 2024)
This research is motivated by economic problems and low levels of education, especially amongyoung women, so that many of them prefer to work in the non-formal sector, one of which is theBanana chips entrepreneurship in Gampong Blang Cot Baroh, Jeumpa District, BireuenRegency. The aim of this research is to find out how young women participate as sellers andwhat factors are behind them becoming sellers. This research uses a qualitative approach withdescriptive methods. Data collection techniques through observation, interviews anddocumentation with 15 informants. From the research results, it was found that young womenparticipated directly in the form of real energy provided. There are two types of participation,namely participation in sales and promotional activities. In sales activities, there are four tasksfor young women, namely calling buyers, serving buyers and refilling merchandise. Inpromotional activities, young women use promotional techniques using WOM, namely WOMintensity, Positive Valance WOM, and WOM Content. The recruitment process for femalesalespeople is very simple. The indicators measuring the work ethic of women sellers are hardwork, discipline, honesty, responsibility and diligence. The factors behind young women workingas sellers are economic factors, where young women work to fulfill economic needs, have familyresponsibilities, and the desire to work to be financially independent and finance personal needs.Keywords: Participation, Young Women, Entrepreneurship